Sucrose synthase activity does not restrict glycolysis in roots of transgenic potato plants under hypoxic conditions - Sonnewald, Uwe; et al. (Planta, 1999)
The effect of hypoxia on root development and carbon metabolism was studied using potato (Solanum tuberosum L.) plants as a model system. Hypoxia led to a cessation of root elongation, and finally to the death of meristematic cells. These changes were accompanied by a 4- to 5-fold accumulation of hexoses, suggesting that insufficient carbohydrate supply was not the cause of cell death. Tn addition, prolonged hypoxia (96 h) resulted in a 50% increase in activity of most glycolytic enzymes studied and the accumulation of glycerate-3-phosphate and phosphoenolpyruvate. This indicates that end product utilisation may restrict metabolic flux through glycolysis. As expected, the activities of alcohol dehydrogenase (EC 1.1.1.1) and pyruvate decarboxylase (EC 4.1.1.17) increased during hypoxia. Apart from the enzymes of ethanolic fermentation the activity of sucrose synthase (SuSy; EC 2.4.1.13) was enhanced. To investigate the in-vivo significance of this increase, transgenic plants with reduced SuSy activity were analysed. Compared to untransformed controls, transgenic plants showed a reduced ability to resume growth after re-aeration, emphasising the crucial role of SuSy in the toleration of hypoxia. Surprisingly, analysis of glycolytic intermediates in root extracts from SuSy antisense plants revealed no change as compared to wildtype plants. Therefore, limitation of glycolysis is most likely not responsible for the observed decreased ability for recovery after prolonged oxygen starvation. We assume that the function of SuSy during hypoxia might be to channel excess carbohydrates into cell wall polymers for later consumption rather than fuelling glycolysis.
Keywords: carbohydrate metabolism; glycolysis; hypoxia; Solanum; Sucrose synthase; Transgenic potato